DETERMINANT TAX AVOIDANCE IN BASIC AND CHEMICAL INDUSTRY MANUFACTURING COMPANIES LISTED ON THE IDX - Hamilah Hamilah; Kenny F. Situmorang (Sosiohumaniora, 2021)
Profitability is one factor to attribute the company’s financial condition to tax avoidance. Leverage is a ratio to measure a company’s ability to pay all its liabilities both short-term and long-term. In addition to profitability and leverage, sales growth can also affect tax avoidance activities. By measuring the sales growth of a company can predict how much profit it earns so that the company will tend to practice tax avoidance. The purpose of this research is to build a theory that serves to explain a relationship. The relationship used is a causal relationship that influences variables and other variables. The study uses quantitative research methods with a causal descriptive and associative approach to determine the influence between two or more variables. The test results showed that returns on assets, debt to equity ratio, and sales growth affected the cash effective tax rate.f research